Retraction Hooks of Different Lengths for Maxillary Whole Arch Distalization with Miniscrew Anchorage : A Finite Element Analysis - Vanichaya Tangsumroengvong (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Objectives: To evaluate the von Mises stress distribution in the periodontal ligament and the displacement pattern of maxillary whole arch distalization applied to retraction hooks of different lengths with miniscrew anchorage and to determine the optimal length of retraction hook, using the finite element method. Methods: A finite element model of maxillary teeth with periodontal ligament and alveolar bone was constructed. The miniscrews were placed bilaterally 6 mm above the buccal cemento-enamel junction at the modified infrazygomatic crest site. The distalization force of 200g was applied to 0-, 2-, 4-, 6-, 8-mm length retraction hooks located between the lateral incisor and canine. The stress distribution in the periodontal ligament and the displacement of the teeth were analyzed. The optimal length of retraction hook for maximal distal movement of the maxillary whole arch along the occlusal plane was investigated. Results: The von Mises stress in the anterior teeth was greater than in the posterior teeth with all hook lengths. With the 0-mm and 2-mm lengths, the anterior teeth were extruded and tipped palatally; the posterior teeth were intruded and tipped distally. With the 4-mm length, all maxillary teeth were distalized along the occlusal plane with minimal movement in the vertical direction. The anterior teeth were slightly tipped labially; the posterior teeth were slightly tipped distally. With the 6-mm and 8-mm lengths, the anterior teeth were intruded and tipped labially; the posterior teeth were extruded and tipped distally. The optimal length in this study was found to be 4 mm. Conclusions: Different lengths of retraction hook resulted in different patterns of stress distribution in the PDL and in different patterns of displacement of the maxillary teeth in whole arch distalization. The optimal length of retraction hook was 4 mm for maximal distal movement of the maxillary whole arch along the occlusal plane.